Faults Analysis Theory and Schemes of Three-Phase Power Systems - Chatterjee, Shubhadip; Khan, Afjal (International Journal of Computer Sciences and Engineering, 2025)
In this paper the analysis of unsymmetrical transversal faults that can occur on a three-phase networks is presented by means of Fortescue Symmetrical Component Transformation (SCT). The various types of fault are analyzed and the connections between sequence networks and the related sequence equations are used to evaluate the phase fault currents. The obtained results are compared with those obtained for three-phase and six-phase systems. The related considerations are also extended to the generic n-phase systems.